Hafnia alvei: A new pathogen in open fractures. (April 2017) - Litrenta, Jody; Oetgen, Matthew
Abstract: Background: Deep infection following open both bone forearm fractures is a rare complication. Prophylactic antibiotic regimens are targeted at the most common pathogens, which include primarily Staph aureus followed by gram-negative bacteria. Hafnia alvei is an unusual pathogen that is rarely pathogenic in humans and has never been reported as a cause of infection following open fracture. Methods: We present a 12-year-old male with an open forearm fracture who developed a late deep infection. Cultures grew only Hafnia alvei . The patient was treated with debridement, placement of antibiotic beads, and ciprofloxacin. Results: At 6 months following the initial debridement, the patient had no clinical evidence of infection and regained full function of the affected forearm without any residual deficits. Conclusions: This is the first report of deep infection following an open forearm fracture owing to Hafnia alvei, a pathogen rarely responsible for human infection.